Complete heart block in patients infected with SARS-CoV-2: A case series from a developing country. (September 2021) - Sharif, Muhammad Hammad; Khan, Abdul Wali; Khaleeque, Madeeha; Haffar, Ammer; Jaiswal, Vikash; Song, David; Abdelghffar, Mohamed; Ahmad, Saad; Almas, Talal; Hanif, Muhammad
Abstract: Coronavirus Disease 19 (COVID-19) has led to a global pandemic and has been the center of attention across the entire medical community. This novel virus was initially thought to affect primarily the respiratory system, but now it is evident that it has a multitude of effects on the human body. Our point of interest is to establish the effect of COVID-19 infection on the conducting system of the heart. We present a case series of four patients who developed complete heart block (CHB) shortly after being infected with COVID-19 without any previous known risk factors of complete heart block. There have only been a few previous case reports on the occurrence of CHB in COVID-19 patients highlighting the importance and the need of our case series to the literature of cardiovascular outcomes in COVID-19 patients. Our case series highlight that COVID-19 can indeed affect the conduction system of the heart and cause CHB in patients who then recovered spontaneously further elucidating the transient nature of cardiovascular effects caused by the novel virus. Highlights: COVID-19 was initially thought to affect primarily the respiratory system, but now it is evident that it has a multitude of effects on the human body including the conduction system of the heart that can cause complete heart block (CHB). Other etiologies of CHB must be ruled out including ischemic heart disease, hyperkalemia, hypothyroidism, infections and rate limiting drugs affecting the AV node conduction including BB, CCB, and digoxin. There are many potential effects of COVID-19 and CHB should be considered and close monitoring with telemetry will be beneficial.